AN ANALYSIS OF DALALAH AL-ALFADH (LEGAL SEMANTICS) IN MAJMA' FIQH AL-ISLAMI FATWAS CONCERNING THE DIGITAL ECONOMY THE RELATIONSHIP BETWEEN ARABIC LINGUISTIC STRUCTURE AND LEGAL CONCLUSIONS - Faisol; Muhammad A'inul Haq (MIYAH: Jurnal Studi Islam, 2026)
The rapid disruption of the digital economy necessitates adaptive legal responses from Islamic jurisprudence. This study aims to analyze the application of Dalalah Al-Alfadh (legal semantics) in the fatwas of Majma' Fiqh Al-Islami ad-Dawli concerning digital economic instruments, determining how Arabic linguistic structures shape legal conclusions. Employing a qualitative library research design, this study utilizes an interdisciplinary approach that integrates semantics and ushul fiqh (Islamic legal theory). Data were collected from official fatwa documents and analyzed using textual discourse analysis. The results reveal that the fatwa authority actively engages in "linguistic ijtihad" through two primary mechanisms. First, the application of Taqyid Al-Mutlaq (restriction of absolute meaning) to the terminology of Naqd (currency) delegitimizes pure cryptocurrency by limiting the definition to state-issued instruments, thereby establishing the presence of gharar (uncertainty). Second, the application of Tausi' Dalalah Al-Ibarah (expansion of explicit meaning) to al-Mu'athat (action-based contracts) legitimizes algorithmic smart contracts by legally equating computer codes with human contracting intent. This study concludes that in contemporary Islamic jurisprudence, the Arabic language functions not merely as a communicative medium but as a fundamental generator of law. These findings strongly implicate the need for an academic reorientation in Arabic Language Education programs, recommending the integration of critical legal literacy into the pedagogical curriculum to bridge the gap between mechanical grammatical mastery and contemporary legal analysis.